H Syndrome with Atypical Presentation - A Diagnostic Enigma - Sowmya S. Aithal; Vinupriya Sakkaravarthi; K. Gopalakrishnan; Anitha Chakravarthy (Wolters Kluwer Medknow Publications, 2024)
H syndrome is a rare autosomal recessive genodermatosis characterized by cutaneous manifestations and other systemic involvement. It presents with features like hyperpigmentation, hypertrichosis, hepatosplenomegaly, hearing loss, hallux valgus, hyperglycemia, low height, hypogonadism, and heart anomalies. Without a high index of suspicion, it is often misdiagnosed with other sclerodermatous cutaneous disorders. This case report highlights the clinical variability of H syndrome. An 8-year-old female child presented with hyperpigmented, hypertrichotic indurated patches with hyperglycemia and short stature. Histopathology showed dense lymphohistiocytic infiltrate and fibrosis in the dermis and subcutaneous tissue. The patient lacked features like heart anomalies, hearing loss, and hallux valgus, suggesting forme fruste presentation of H syndrome. An overlap between features of H syndrome and PHID syndrome is also suspected because of atypical presentation.